2016
DOI: 10.1016/j.ebiom.2015.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of Metabolic Syndrome-Associated Cognitive Impairments in Mice via a Reduction in Dietary Fat Content or Infusion of Non-Diabetic Plasma

Abstract: Obesity, metabolic syndrome (MetS) and type 2 diabetes (T2D) are associated with decreased cognitive function. While weight loss and T2D remission result in improvements in metabolism and vascular function, it is less clear if these benefits extend to cognitive performance. Here, we highlight the malleable nature of MetS-associated cognitive dysfunction using a mouse model of high fat diet (HFD)-induced MetS. While learning and memory was generally unaffected in mice with type 1 diabetes (T1D), multiple cognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
48
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 106 publications
7
48
0
Order By: Relevance
“…We also found IL-12p70 and IL-13 to be closely related to high insulin levels in APP/PS1xdb/db mice, both of which have been shown to be elevated in prediabetic patients [62]. A similar trend has been observed for IL-12p70 in HFD-fed mice [91]. Altogether, multivariate analysis of cytokine expression in the cortex from our mixed model indicates that there are marked proinflammatory differences in cytokine profiles associated with the co-presentation of T2D and AD pathologies.…”
Section: Discussionsupporting
confidence: 79%
“…We also found IL-12p70 and IL-13 to be closely related to high insulin levels in APP/PS1xdb/db mice, both of which have been shown to be elevated in prediabetic patients [62]. A similar trend has been observed for IL-12p70 in HFD-fed mice [91]. Altogether, multivariate analysis of cytokine expression in the cortex from our mixed model indicates that there are marked proinflammatory differences in cytokine profiles associated with the co-presentation of T2D and AD pathologies.…”
Section: Discussionsupporting
confidence: 79%
“…Interestingly, the cognitive impairments we observed in HFD fed E3 and E4 mice were not observed in a model of Type 1 Diabetes (T1D) – as we have previously observed in wildtype mice22 – suggesting that these negative cognitive effects are specific to the background of HFD-induced obesity and IR. However, many studies have demonstrated cognitive dysfunction in rodent models of T1D,23 and discrepancies with our results could be due to a number of factors including mouse age, sex and strain, the specific cognitive tasks employed, and delivery method of STZ (intracerebroventricular vs intraperitoneal vs intravenous).…”
Section: Discussionsupporting
confidence: 70%
“…108 Finally, animal studies support the findings in man and also demonstrate that resolving obesity improves cognitive performance. 109111 Switching mice from a HFD to a regular diet to reduce caloric intake results in improved metabolic health, with increased insulin sensitivity and improvement in cognitive function. These improvements are associated with reduced blood brain barrier-leakage, decreased glial activation, and increased vascular perfusion.…”
Section: Neurological Benefits Of Targeting Obesitymentioning
confidence: 99%
“…These improvements are associated with reduced blood brain barrier-leakage, decreased glial activation, and increased vascular perfusion. 109111 …”
Section: Neurological Benefits Of Targeting Obesitymentioning
confidence: 99%